The South China Sea disputes : formula for a paradigm shift- a rejoinder - Robert C. Beckman (2014)
Our proposal that China bring its maritime claims into comformity with law and UNCLOS in particular has been critiqued by Professor Raul 'Pete' Pedrozo of the US Naval War College as "problematic" and "counterproductive". We beg to differ. While he offers an interesting perspective and is entitked to his own views of China's policy on the South China Sea, we believe that several of his points warrant a rejoinder.